EDUKASI KESEHATAN DAN PELATIHAN BANTUAN HIDUP DASAR (BHD) PADA MASYARAKAT DI DESA LEMPUR KABUPATEN KERINCI - Erwinsyah, Erwinsyah; Wahyuni, Tri; Samsinar, Samsinar; Asmeriyani, Asmeriyani; Dormina, Dormina (STIKES Garuda Putih, 2024)
An emergency is a life-threatening situation that must be taken immediately to avoiddisability or even death of the victim. The success of assistance to emergency sufferers is verydependent on the speed and accuracy in carrying out the initial assessment which will determine theform of assistance that will be given to the patient.Objective: health education activities and basic life support (BHD) training for the community inLempur village, Kerinci districtMethod: community service activities ran smoothly in Lempur Village with a total of 10 participants.The methods used are lectures, discussions and demonstrations.Results: Shows an increase in knowledge about basic life support in the Lempur Village community inKerinci Regency. It can be stated that during the activity the participants were very enthusiastic. Thiscan be seen from the number of participants who asked questions and paid attention to the informationprovided. At the end of this outreach, the community monitored the behavior of participants in basiclife support outreach in the Lempur Village community, Kerinci Regency.Conclusion: After being given health education and practical work on basic life support, the people ofLempur Village already know the procedures for providing basic life support to help victims who experience cardiac arrest and airway obstruction. where the people of Lempur Village are willing tofollow good basic life support methods provided by material and practicum providers